Treatment of selected Halogenated Organic Compounds in Water using Colloidal Silver Nanocatalysts under Reducing Borohydride Conditions - Adan , Tadicha; Victor Wandera , Opondo; Aloice , Ogweno; Ali , Shee (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Halogenated organic compounds (HOCs) are frequently encountered water contaminants. They are widely used as solvents or feed stocks in the production of paints, adhesives, lacquerers, pharmaceuticals and veterinary drugs, cosmetics, pesticides and herbicides. Most HOCs are recalcitrant, toxic and possible carcinogens. HOCs treatment in water may involve physical, biological and chemical processes. Chemical treatment via oxidation or reduction processes are preferred due to their ability to transform HOCs into environmental benign products. Compared to reduction, oxidation may produce toxic byproducts and thus for complete mineralization, huge amounts of redox equivalents are needed. Reductive dehalogenation is selective and more suited for HOCs treatment. It may employ electrocatalysts, metal catalysts and reagents. Nanoscale zero valent iron (nZVI) as an electron-releasing reagent is environmentally compatible but ineffective for transformation of saturated aliphatic HOCs containing < 2 Cl-atoms. Noble metals such as Pt, Rh and Pd are excellent hydrogenation catalysts for HOCs reduction but are expensive and susceptible to deactivation in water. Metallic Ag (Ag0) is a promising electrocatalyst for dechlorination of saturated aliphatic HOCs. Ag is relatively cheaper than the noble metals and is sparingly stable in water. Despite this potential, colloidal Ag0 catalysts have received less attention for HOCs treatment. In this study, optimal conditions were established for synthesis of colloidal Ag0 catalyst using sodium borohydride (NaBH4). Calculated Ag0 activities for reduction of dibromomethane, monobromomethane, perchloroethylene, trichloroethylene and vinylbromide were 86.92 ± 2.61, 3.45 ± 0.17, 2.38 ± 0.07, 1.16 ± 0.05 and 3.21 ± 0.10, respectively. The reduction of diclofenac and bromocresol blue by Ag0+NaBH4 was slow and incomplete due to catalyst deactivation. Thus, Ag0+NaBH4 is more appropriate for reduction of aliphatic and olefinic C—Cl and C—Br bonds.